2013
DOI: 10.1177/1538192713513464
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Behavioral and Cognitive Cultural Orientation on Mexican American College Students’ Life Satisfaction

Abstract: We examined the role of behavioral (acculturation and enculturation) and cognitive cultural orientation (independent and interdependent self-construal) on Mexican American college students' life satisfaction. Analyses explained 28% of the variance in life satisfaction, with social class, grade point average, and independent self-construal being unique predictors. Furthermore, enculturation was associated with increasing life satisfaction among those low in interdependent self-construal, whereas acculturation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Our study contributes to the understanding of subjective happiness in Mexican American college students by exploring the relationship among humanistic and family factors with subjective happiness. It augments previous studies (Ojeda, Castillo, et al, 2014;Ojeda, Edwards, et al, 2014;Vela, Castro, et al, 2015; on Mexican American college students' happiness. The results of our investigation are important given the relationship among happiness, academic achievement, educational goals, resilience, and career satisfaction (Gabriele, 2008;Lyubomirsky et al, 2005;Marques et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our study contributes to the understanding of subjective happiness in Mexican American college students by exploring the relationship among humanistic and family factors with subjective happiness. It augments previous studies (Ojeda, Castillo, et al, 2014;Ojeda, Edwards, et al, 2014;Vela, Castro, et al, 2015; on Mexican American college students' happiness. The results of our investigation are important given the relationship among happiness, academic achievement, educational goals, resilience, and career satisfaction (Gabriele, 2008;Lyubomirsky et al, 2005;Marques et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…As a result, we explored the following research question: To what extent does meaning in life, search for meaning in life, hope, familism, and self-efficacy influence Mexican American college students' subjective happiness? We build on previous studies (Ojeda, Castillo, et al, 2014;Ojeda, Edwards, Hardin, & Pina-Watson, 2014;Vela, Castro, et al, 2015; by including different factors that might influence Mexican American students' subjective happiness.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…Life satisfaction refers to perceptions of quality of life as well as positive and negative affect (Diener, Luca, & Oishi, ). Researchers have found that life satisfaction is related to academic achievement, college retention (Frisch et al, ), academic satisfaction, college self‐efficacy (Ojeda, Flores, & Navarro, ), and college persistence (Ojeda, Edwards, Hardin, & Piña‐Watson, ). In addition, Kaya, Tansey, Melekoǧlu, and Çakıroǧlu () found that academic stress had a negative relationship to life satisfaction.…”
Section: Life Satisfactionmentioning
confidence: 99%
“…In summary, researchers have found theoretical and empirical relationships among positive psychology, cultural, and family factors . Acculturation was related to Hispanic girls' career decision self-efficacy (Ojeda, Piña-Watson, et al ., 2011), enculturation was related to Mexican Americans' life satisfaction (Ojeda, Edwards, Hardin, & Piña-Watson, 2014), and meaning in life and family importance were related to Mexican American high school students' vocational outcome expectations . However, these variables have been examined separately in previous studies; researchers have not included these factors in a single model to determine which factors have the strongest predictive relationship on Latina/o students' vocational outcome expectations .…”
Section: Family and Cultural Factorsmentioning
confidence: 99%